Pengaruh Harga, Kualitas Produk Dan Suasana Toko Terhadap Loyalitas Konsumen Ompu Gende Coffee - Purnama, Nadia Ika; Harahap, Seprida Hanum; Siregar, Dini Syahputri (Lembaga Riset Ilmiah, 2022)
This study aims to see and determine the effect of price, product quality, and store atmosphere on consumer loyalty to Ompu Gende Coffee. This research is associative quantitative research, namely research to examine the effect of the independent variable and the dependent variable. The population in this study was 80 consumers of Ompu Gende Coffee. The data collection technique used in this research is a questionnaire. But in practice, the data processing of this research is not processed manually, but using the statistical software package social for sciences (SPSS26) with multiple analysis techniques, classical assumptions, hypothesis testing, and coefficient of determination. The results of this study indicate that price, product quality, and store atmosphere on consumer loyalty